2022
DOI: 10.1021/acs.macromol.2c01486
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Sulfonated Co-Polynaphthoyleneimide Proton Exchange Membranes with Different Ratios of Hydrophylic to Hydrophobic Groups Studied Using SFG NMR

Abstract: We use static field gradient (SFG) NMR to determine the self-diffusion coefficients of protons in fluorine-free sulfonated co-polynaphthoyleneimide (co-PNIS) proton exchange membranes with different ratios of hydrophilic to hydrophobic groups. The investigations were carried out in the temperature range from 193 to 355 K. Because there are protons not only in water but also in the polymer framework, 1H NMR diffusion studies of these membranes may suffer from cross-relaxation effects between the different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…17 O-enriched (90%) water ( 1 H 2 17 O) was purchased from Cambridge Isotope Labs, and the Nafion 212 membrane was obtained from Chemours (USA). For cleaning, the standard procedure was applied. , The membranes were boiled in a 3 wt % hydrogen peroxide solution for 1 h, washed with distilled water to eliminate any organic contaminants, and boiled in distilled water for an additional 1 h to ensure that all hydrogen peroxide residue was removed. The final protonation procedure included exposure to 0.5 M sulfuric acid for 1 h, followed by double boiling in distilled water for an additional 1 h. The purified and protonated membrane was cut into 1 cm × 10 cm stripes, which were annealed at 80 °C in a vacuum of 0.1 bar for 20 h and subsequently kept at 25 °C under 0.1 bar for 20 h before they were rolled and inserted into NMR tubes.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 O-enriched (90%) water ( 1 H 2 17 O) was purchased from Cambridge Isotope Labs, and the Nafion 212 membrane was obtained from Chemours (USA). For cleaning, the standard procedure was applied. , The membranes were boiled in a 3 wt % hydrogen peroxide solution for 1 h, washed with distilled water to eliminate any organic contaminants, and boiled in distilled water for an additional 1 h to ensure that all hydrogen peroxide residue was removed. The final protonation procedure included exposure to 0.5 M sulfuric acid for 1 h, followed by double boiling in distilled water for an additional 1 h. The purified and protonated membrane was cut into 1 cm × 10 cm stripes, which were annealed at 80 °C in a vacuum of 0.1 bar for 20 h and subsequently kept at 25 °C under 0.1 bar for 20 h before they were rolled and inserted into NMR tubes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The factor exp(−t m /T 1 ) considers the additional damping of the STE signal S q (t m ) by spin−lattice relaxation. Because we controlled t m and t e in the STE sequence and predetermined T 1 in independent relaxation measurements or removed relaxation effects by performing measurements for different gradient strengths g, 27 diffusion coefficient D was the only free parameter when we fitted S q (t m ) data. To ensure the best possible comparison of the D H and D O values from 1 H and 17 O NMR studies, we used similar q values for both nuclei; i.e., we adjusted evolution times t e to compensate for the different gyromagnetic ratios γ of 1 H and 17 O.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, it was shown that hydrocarbon polymers of the polynaphthoyleneimide class (further co-PNIS) were notable because of their high transport characteristics [ 32 , 33 ]. The production of proton-exchanged membranes from sulfonated polynaphtoyleneimides (SPNI) based on industrial 1,4,5,8-naphthalene tetracarboxylic acid (NTDA) anhydride with six-membered imide rings was carried out in a number of works [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theories on the effects of ionomer structure [13][14][15] and environmental factors [16][17][18][19][20] (e.g., temperature, humidity) on the proton transport mechanism are now well established. For instance, when the water content in the membrane increases, hydrogen bonds are formed and broken between water and hydrated hydrogen ions (H 3 O + ), allowing proton transfer via the water bridges.…”
mentioning
confidence: 99%